2020
DOI: 10.2147/cmar.s227501
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Analysis of 15 Cases of Gallbladder Neuroendocrine Carcinoma and Comparison with Gallbladder Adenocarcinoma Using a Propensity Score Matching</p>

Abstract: This study aimed to investigate the clinicopathological features and prognosis of gallbladder neuroendocrine carcinoma (GB-NEC). Patients and Methods: Fifteen patients with GB-NEC and 171 patients with gallbladder adenocarcinoma (GB-ADC) treated in two tertiary medical centers between 2009 and 2015 were included. The clinicopathological features and prognostic risk factors of GB-NEC were analyzed retrospectively. A propensity score matching in a 1:2 ratio was used to compare the prognosis of GB-NEC and GB-ADC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 30 publications
4
58
2
Order By: Relevance
“…Chemotherapy is critical for patients with unresectable GB-NECs, and can improve survival. [ 12 , 15 ] In our study, compared with the patients who only received surgery, the patients who underwent postoperatively chemotherapy lived longer with a median survival time of 8.9 and 2.2 months, respectively. Cisplatin or carboplatin plus etoposide were generally recommended as the primary program for poorly differentiated GB-NECs and achieved satisfactory responses.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Chemotherapy is critical for patients with unresectable GB-NECs, and can improve survival. [ 12 , 15 ] In our study, compared with the patients who only received surgery, the patients who underwent postoperatively chemotherapy lived longer with a median survival time of 8.9 and 2.2 months, respectively. Cisplatin or carboplatin plus etoposide were generally recommended as the primary program for poorly differentiated GB-NECs and achieved satisfactory responses.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, no secretory symptoms were observed even in the patients with distant metastasis and upper abdominal pain was the most common symptom, consistent with most previous literatures. [ 11 , 12 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Yun study did not support this hypothesis, with the overall five-year survival rate of GB-NEC higher than GB-ADC. [ 56 ] Suspecting that confounding factors between the 2 groups might affect the result, Yan et al [ 5 ] used propensity score matching to reduce the influence of confounding factors between the 2 groups, and the results still showed that GB-NEC had worse prognosis than GB-ADC. The comparison of these studies was shown in Table 2 .…”
Section: Prognosismentioning
confidence: 99%
“…However, unlike NENs from the gastrointestinal tract or respiratory tract, GB-NECs are mostly asymptomatic. [ 5 ] Due to fact that GB-NEC is lack of special clinical manifestations and typical imaging features, it is difficult to distinguish GB-NEC from gallbladder adenocarcinoma (GB-ADC) without pathological examination. Additionally, there is currently no consensus on the surgical strategy and guidelines of GB-NEC.…”
Section: Introductionmentioning
confidence: 99%